ECONOMICS OF ENOUGH AND ETHICS OF CARE FOR A PROSPEROUS AND SUSTAINABLE LIFE - Nandhikkara, Jose (Journal of Dharma, 2021)
An economics of enough and care could and should replace the hedonistic consumerism, liberate the poor from unjust and unbearable poverty, and provide sustainable prosperity for people and the planet. We need to make an economic and ethical conversion from the madness of more to the wisdom of enough. We are not just hedonistic, novelty-seeking, and selfish consumers. We care for the planet and all those who live in our common home. Sustainable prosperity could only be shared prosperity. Our wellbeing depends on each of us having the resources we need to meet our fundamental rights to food, water, health, education, housing, energy; our wellbeing also depends on our planetary home, the Earth. The fact that all human beings are sisters and brothers living in the common home, the Earth, together with other living beings, is a fundamental fact of life that calls for a fundamental moral vision and mission to treat everyone as siblings and practice ethics of care. Human beings are entrusted with the care of the Earth and all those who live in it. A planet-based and people-centred economy is necessary for sustainable prosperity.